2020
DOI: 10.1177/1559325820916949
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A and the Risk of Obesity a Systematic Review With Meta-Analysis of the Epidemiological Evidence

Abstract: Bisphenol A (BPA) is suspected to be associated with several chronic metabolic diseases. The aim of the present study was to review previous epidemiological studies that examined the relationship between BPA exposure and the risk of obesity. PubMed, Web of Science, and Embase databases were systematically searched by 2 independent investigators for articles published from the start of database coverage until January 1, 2020. Subsequently, the reference list of each relevant article was scanned for any other po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…A recent meta-analysis of data collected in adults and children reported a dose–response analysis of different studies. This analysis found that a 1 ng/mL increase in BPA levels increased the risk of obesity by around 11% [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of data collected in adults and children reported a dose–response analysis of different studies. This analysis found that a 1 ng/mL increase in BPA levels increased the risk of obesity by around 11% [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature review shows that BPA is not only an endocrine-disrupting chemical, but it also causes damage to hepatocytes through oxidative stress (Kourouma et al 2015 ; Elswefy et al 2016 ; Li et al 2017 ). BPA can modulate the immune response, has mutagenic activity toward eukaryotic cells, and leads to obesity (Michałowicz 2014 ; Wu et al 2020b ). Moreover, BPA disrupts microtubule organization and centrosome function, hence showing the vast spectrum of cancer-promoting effects, including induction of prostate and mammary cancer formation (Seachrist et al 2016 ; Ho et al 2017 ; Mesnage et al 2017 ).…”
Section: Endocrine-disrupting Chemicalsmentioning
confidence: 99%
“…Indeed, BPA accumulates in adipose tissue and increases the number and size of adipocytes, thus contributing to increased adiposity and weight gain [ 16 ]. Moreover, a recent systematic review with a meta-analysis of the relevant epidemiological evidence reported that BPA exposure shows a significant positive association with indices of both generalized and central/abdominal obesity [ 17 , 18 ]. Similarly, systematic review data also support a relationship between BPA exposure and type 2 diabetes (T2DM) [ 19 ].…”
Section: Bpa and Comorbidities Predisposing To Severe Covid-19mentioning
confidence: 99%